Perspektif Kekuatan Pembuktian Keterangan Saksi dalam Perkara Tindak Pidana Pencurian (Studi Kasus Perkara Nomor:LP/B/05/V/RES.1.8/2025/SPKT.UNITRESKRIM/POLSEK TEMPULING) - Syarwani Syahril; Vivi Arfiani Siregar; KMS Novyar Satriawan F (Indragiri Law Review, 2026)
This study aims to analyze the perspective of the evidentiary strength of witness testimony in theft cases based on Case Number LP/B/05/V/RES.1.8/2025/ SPKT.UNITRESKRIM/POLSEK TEMP ULING and to identify the factors influencing its evidentiary value. The research employed an empirical legal method with a descriptive-analytical approach, combining normative juridical and empirical juridical perspectives. Data were collected through interviews, observations, and library research and were analyzed qualitatively. The findings indicate that witness testimony constitutes a valid form of evidence under the Indonesian Code of Criminal Procedure (KUHAP), although its evidentiary strength must be supported by other legal evidence to establish the conviction of law enforcement officers. Factors affecting the evidentiary value include witness credibility, direct knowledge of the incident, consistency of testimony, conformity with other evidence, and investigator professionalism. Strengthening witness examination and corroborating evidence are essential to ensuring objective proof, legal certainty, and the attainment of material truth.